Readiness to reduce primary care-associated carbon emissions in England: a cross-sectional survey of clinical and non-clinical staff views - Jeremy Dale; Ana Raquel Nunes; Rachel Spencer; Helen Twohig; Florence Karaba; Olivia Geddes; Frederik Dahlmann; Abigail Eccles (BMJ Open, 2025)
Objectives To describe current levels of interest and action around decarbonisation in general practice settings, and awareness and use of currently available materials designed to support general practice teams undertake decarbonisation activity.Design Cross-sectional, mixed methods, online survey.Setting 473 general practices in three Integrated Care Board regions in England.Participants Multiprofessional general practice staff.Results There were 328 responses from 163 (34.5%) practices. Most respondents were general practitioner (GP) partners (98; 29.9%), other clinical staff (93; 28.3%) or managerial staff (76; 23.2%). 229 (69.8%) respondents felt that acting to reduce carbon emissions from primary care is a legitimate part of general practice activity. However, only 44 (13.4%) felt that there is sufficient training and resources to support such activity, and only 59 (18.0%) agreed that there was sufficient leadership from higher levels within the health service to enable this. 58 (35.6%) practices had a lead for sustainability, generally managerial staff (22; 37.9%) or GP partners (17; 29.3%). Compared to other practices, those with a decarbonisation lead reported increased levels of decarbonisation actions currently being undertaken (mean = 5.2 vs 3.1; t(161) = 7.7, p<0.001); use of resource materials that support decarbonisation (79.3% vs 32.3%; χ2=31.9, p<0.001); and planned future decarbonisation actions (63.8% vs 15.2%; χ2=32.3, p<0.001). Respondents from 47 (28.8%) practices provided free-text comment, mostly noting conflicting workload priorities, limited funding, lack of leadership and practice staff engagement as barriers to decarbonisation activity in their practice.Conclusions This survey provides insight into how English general practices and their staff regard decarbonisation activities. The findings highlight the importance of leadership, resources and incentives in driving such activities and have implications for initiatives to help achieve wider decarbonisation goals in healthcare.